Age‐associated decrease of senescence marker protein‐30/gluconolactonase in individual mouse liver cells: Immunohistochemistry and immunofluorescence. Issue 6 (14th October 2014) - Ishigami, Akihito; Masutomi, Hirofumi; Handa, Setsuko; Maruyama, Naoki
<x xml:space="preserve">Abstract</x> Aim Senescence marker protein‐30 (SMP30)/gluconolactonase (GNL) is an age‐associated protein in that its presence decreases with aging. Here, we used immunohistochemical analysis to investigate the changes of SMP30/GNL in individual cells of the liver from progressively aged mice. Methods Male C57BL/6 strain mice at 1, 3, 6, 12, 24 and 30 months‐of‐age were the source of hepatic cells used to detect SMP30/GNL. Liver sections from these mice were subjected to immunohistochemical staining with anti‐SMP30/GNL antibody. For immunofluorescent staining, primary cultured hepatocytes from mice at various ages were stained with SMP30/GNL and albumin. Results In liver cells from mice of all ages, SMP30/GNL staining appeared in some but not all parenchymal cells, and localized in both the nuclei and cytoplasm. Moreover, SMP30/GNL‐positive staining of parenchymal cells was present only around central vein areas, but not at sites of portal veins. Furthermore, the number of SMP30/GNL‐positive cells increased as mice aged from 1 to 12 months, then decreased from the 12th to 24th month. Results were similar in primary cultured hepatocytes from mice of various ages. Conclusions SMP30/GNL‐positive cells localized mainly around the central veins in the livers of mice and decreased numerically with aging, although there was no age‐related change in counts of albumin‐positive cells. SMP30/GNL protein occupied the nuclei and cytoplasm. Therefore, nuclear SMP30/GNL protein might be a regulatory factor specific for genes whose expression governs transcription and the aging process. Geriatr Gerontol Int 2015; 15: 804–810.